THE MANUFACTURING OF PHARMACEUTICAL INGREDIENTS IN RUSSIAN FEDERATION: THE CRISIS AT THE TURN OF XX TO XXI CENTURIES - E. V. Denisova (Разработка и регистрация лекарственных средств)
The tendencies of development of the pharmaceutical ingredients production at the turn of the XX century in Russia were analysed. During this period, the production of pharmaceutical ingredients turned into a state of deep crisis. The reason for crisis were the sharp decrease of production volumes, production capacities and the level of their load, the practical termination of R&D in creation and introduction of new domestic original drugs. The macroeconomic and industry-specific causes of this crisis were identified. Since market mechanisms at the turn of the XX and XXI centuries in Russia were not able to ensure the withdrawal of the development and production of pharmaceutical ingredients from the crisis, therefore, government support measures that were provided for by the Federal Target Program «Development of the pharmaceutical and medical industry of the Russian Federation for the period Until 2020 and a further perspective» and are implemented in the process of its effectuation.